From Industrial City to Sustainable City. The Northern Suburbs of Paris Yesterday and Today - Lebeau, Boris (European Spatial Research and Policy, 2014)
Former industrial suburbs, which are now the object of economic and functional transformations almost everywhere in Europe, are suitable testing grounds for implementing a more sustainable urban development. The case of the northern suburbs of Paris, which we will look at here, shows that there is no lack of political will or regulatory tools for imagining and planning this sustainable city. However, the social problems that affect these suburbs are a definite impediment to its realization.